Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 91326 by mhmd last updated on 29/Apr/20

Commented by mathmax by abdo last updated on 30/Apr/20

I =∫  (dx/((x−1)^2 (√(x^2 −x+1)))) ⇒ I =_(x−1=t)     ∫  (dt/(t^2 (√((t+1)^2 −(t+1)+1))))  =∫  (dt/(t^2 (√(t^2  +2t+1−t−1+1)))) =∫  (dt/(t^2 (√(t^2 +t+1)))) =∫  (dt/(t^2 (√((t+(1/2))^2 +(3/4)))))  =_(t+(1/2)=((√3)/2) sh(u))     (2/(√3))∫  (1/((((√3)/2)sh(u)−(1/2))^2 ch(u)))×((√3)/2)ch(u)du  =4∫   (du/(((√3)shu−1)^2 )) =4 ∫  (du/(3sh^2 (u)−2(√3)shu +1))  =4 ∫  (du/((3/2)(ch(2u)−1)−2(√3)shu +1)) =8 ∫  (du/(3ch(2u)−3−4(√3)shu+2))  =8 ∫ (du/(3sh(2u)−4(√3)sh(u)−1)) =8 ∫  (du/(3((e^(2u) −e^(−2u) )/2)−4(√3)×((e^u −e^(−u) )/2)−1))  =16 ∫  (du/(3e^(2u) −3e^(−2u)  −4(√3)e^u  +4(√3)e^(−u) −2))  =_(e^u   =z)   16  ∫     (dz/(z(3 z^2 −3z^(−2) −4(√3)z+4(√3)z^(−1) −2)))  =16 ∫  ((z^2  dz)/(z(3z^4 −3−4(√3)z^3  +4(√3)z −2z^2 )))  =16 ∫  ((z^2  dz)/(z(3z^4 −4(√3)z^3 −2z^2  +4(√3)z −3)))  decomposition of F(z) =(z^2 /(z(3z^4 −4(√3)z^3 −2z^2  +4(√3)z −3)))  ...be continued...

I=dx(x1)2x2x+1I=x1=tdtt2(t+1)2(t+1)+1=dtt2t2+2t+1t1+1=dtt2t2+t+1=dtt2(t+12)2+34=t+12=32sh(u)231(32sh(u)12)2ch(u)×32ch(u)du=4du(3shu1)2=4du3sh2(u)23shu+1=4du32(ch(2u)1)23shu+1=8du3ch(2u)343shu+2=8du3sh(2u)43sh(u)1=8du3e2ue2u243×eueu21=16du3e2u3e2u43eu+43eu2=eu=z16dzz(3z23z243z+43z12)=16z2dzz(3z4343z3+43z2z2)=16z2dzz(3z443z32z2+43z3)decompositionofF(z)=z2z(3z443z32z2+43z3)...becontinued...

Answered by MJS last updated on 30/Apr/20

2)  r=(√(x^2 −x+1)) ⇔ x=((1+(√(4r^2 −3)))/2)  r=((√3)/2)cosh s  s=ln t  ⇒ x=(((√3)t^2 +2t−(√3))/(4t)) ⇔ t=((2x−1+2(√(x^2 −x+1)))/(√3))  ∫(dx/((x−1)^2 (√(x^2 −x+1))))=       [t=((2x−1+2(√(x^2 −x+1)))/(√3)) → dx=(((√3)(t^2 +1))/(4t^2 ))dt]  =((16)/3)∫(t/((t−(√3))^2 (t+((√3)/3))^2 ))dt=  =(√3)∫(dt/((t−(√3))^2 ))−((√3)/3)∫(dt/((t+((√3)/3))^2 ))−(1/2)∫(dt/(t−(√3)))+(1/2)∫(dt/(t+((√3)/3)))=  =−((√3)/(t−(√3)))+((√3)/(3t+(√3)))−(1/2)ln (t−(√3)) +(1/2)ln (t+((√3)/3)) =  =−((2((√3)t+3))/((t−(√3))(3t+(√3))))+(1/2)ln ((3t+(√3))/(t−(√3))) =  =−((√(x^2 −x+1))/(x−1))+(1/2)ln ((x+1+2(√(x^2 −x+1)))/(x−1)) +C

2)r=x2x+1x=1+4r232r=32coshss=lntx=3t2+2t34tt=2x1+2x2x+13dx(x1)2x2x+1=[t=2x1+2x2x+13dx=3(t2+1)4t2dt]=163t(t3)2(t+33)2dt==3dt(t3)233dt(t+33)212dtt3+12dtt+33==3t3+33t+312ln(t3)+12ln(t+33)==2(3t+3)(t3)(3t+3)+12ln3t+3t3==x2x+1x1+12lnx+1+2x2x+1x1+C

Answered by MJS last updated on 30/Apr/20

1)  ∫_0 ^π (x/(csc^3  x +cot^2  x csc x))dx=  =∫_0 ^π ((xsin^3  x)/(1+cos^2  x))dx=       by parts       u′=((sin^3  x)/(1+cos^2  x)) → u=^((∗)) cos x −2arctan cos x       v=x → v′=1  =[x(cos x −2arctan cos x)]_0 ^π −∫_0 ^π (cos x −2arctan cos x)dx=       [the integral is zero!]  =π((π/2)−1)

1)π0xcsc3x+cot2xcscxdx==π0xsin3x1+cos2xdx=bypartsu=sin3x1+cos2xu=()cosx2arctancosxv=xv=1=[x(cosx2arctancosx)]0ππ0(cosx2arctancosx)dx=[theintegraliszero!]=π(π21)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com